2001
DOI: 10.1186/bcr303
|View full text |Cite
|
Sign up to set email alerts
|

Reversal effects of nomegestrol acetate on multidrug resistance in adriamycin-resistant MCF7 breast cancer cell line

Abstract: BackgroundChemotherapy is important in the systematic treatment of breast cancer. To enhance the response of tumours to chemotherapy, attention has been focused on agents to reverse multidrug resistance (MDR) and on the sensitivity of tumour cells to chemical drugs. Hundreds of reversal drugs have been found in vitro, but their clinical application has been limited because of their toxicity. The reversal activity of progestogen compounds has been demonstrated. However, classical agents such as progesterone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Compared with other drug transporter inhibitors, a unique advantage of specific ABCG2 inhibitors is the putative role in the elimination of CSCs. Unfortunately, the majority of tested MDR modulators are failed because of either insufficient in efficacy or exhibiting unacceptable toxicity or unpredictable pharmacokinetic interactions [ 9 , 10 ]. Recently, it is reported that ABCG2 has a relatively high affinity with some tyrosine kinase inhibitors (TKIs) which are designed to act by competing against ATP binding to the intracellular catalytic domain of oncogenic tyrosine kinases, thereby inhibiting cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other drug transporter inhibitors, a unique advantage of specific ABCG2 inhibitors is the putative role in the elimination of CSCs. Unfortunately, the majority of tested MDR modulators are failed because of either insufficient in efficacy or exhibiting unacceptable toxicity or unpredictable pharmacokinetic interactions [ 9 , 10 ]. Recently, it is reported that ABCG2 has a relatively high affinity with some tyrosine kinase inhibitors (TKIs) which are designed to act by competing against ATP binding to the intracellular catalytic domain of oncogenic tyrosine kinases, thereby inhibiting cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…These agents antagonize MDR through competitive inhibition of the P-gp-mediated transport of antitumor drugs (2). Generally, the majority of tested compounds are either insufficient in efficacy or exhibit unacceptable toxicity or unpredictable pharmacokinetic interactions (13). There is a need for effective and safe agents that reverse MDR of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although progestin agents appear to stimulate tumor growth under certain conditions [37], one study found that the use of progesterone alone increases breast cancer risk in women [38]. Li et al demonstrated that nomegestrol acetate reverses multi-drug resistance in MCF-7/ADR cells by down-regulating both mRNA and proteins levels of P-gp and markedly increases intracellular adriamycin accumulation [39]. However, the role of PR in BCRP expression in breast cancer remains unknown.…”
Section: Discussionmentioning
confidence: 99%